Weaving Digital Relationships: A Social CRM Case Study of Local Beauty Brands - Asri Ana; Putri Utami Rukmana; Muharman Lubis (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
The Customer Relationship Management paradigm evolved from transaction-based tod collaboration-oriented approach through Social CRM (SCRM) due to digital transformation. Descriptive qualitative research investigates the CRM approaches executed by BLP Beauty and MOP Beauty using digital ethnography and observational methods. The research extends its observation activities to digital platforms including social media platforms and e-commerce platforms and customer review platforms. The analysis proves BLP Beauty uses a standardized omnichannel strategy that adopts community engagement and performs hashtag-based social monitoring and collaborative customer engagement including two additional customer impact channels through Key Opinion Leaders (KOLs) and influencers. BLP Beauty operates with an open and extensive market segmentation whereas MOP Beauty adopts an elite branding strategy with premium positioning. CRM strategies work best when they match the brand image together with key traits of the customer base. The study establishes how vital it is to unite technology and community elements with emotional value creation for developing sustainable customer relations during the current digital era.